Perpetuation of sexual objectification: The role of resource depletion. (7th September 2016) - Tyler, James M.; Calogero, Rachel M.; Adams, Katherine E.
Abstract : Women are sexually objectified when viewed and treated by others as mere objects. Abundant research has examined the negative consequences of being the target of sexual objectification; however, limited attention has focused on the person doing the objectification. Our focus is on the agent and how self‐regulatory resources influence sexual objectification. Consistent with prior evidence, we reasoned that people have a well‐learned automatic response to objectify sexualized women, and as such, we expected objectifying a sexualized (vs. personalized) woman would deplete fewer regulatory resources than not objectifying her. Findings across three studies confirmed our expectations, demonstrating the extent to which people objectify a sexualized woman or not is influenced by the availability of regulatory resources, a case that heretofore has been absent from the literature. These patterns are discussed in the context of the sexual objectification and self‐regulation literature.